2021
DOI: 10.1016/j.jogn.2020.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Synthesis of the Needs of Women Cared for by Midwives During Childbirth in Hospitals

Abstract: Objective: To identify and meta-synthesize results of qualitative studies on the needs of women cared for by midwives during childbirth in hospitals.Data Sources: MEDLINE, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Embase, and the Cochrane Library.Study Selection: We restricted the bibliographic search to articles published in English to July 31, 2020. The initial search yielded 6,407 articles, and after 2,504 duplicates were removed, we screened the titles and abstracts of 3,903 articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
7
0
2
Order By: Relevance
“…In an oft-quoted systematic review of the literature regarding women's satisfaction with childbirth, Hodnett7 identified 4 primary factors determining maternal satisfaction, that is, personal expectations, amount of support from caregivers, the quality of the caregiver-patient relationship, and the patient's involvement in decision making. Support from caregivers during labor is correlated well with maternal satisfaction in other research studies 1,8,9. Another systematic review of prenatal and intrapartum interventions concluded that support for childbearing women, relaxation and pain relief during labor, minimizing obstetric interventions, and preparedness for birth were the most successful strategies for improving the childbirth experience 8.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…In an oft-quoted systematic review of the literature regarding women's satisfaction with childbirth, Hodnett7 identified 4 primary factors determining maternal satisfaction, that is, personal expectations, amount of support from caregivers, the quality of the caregiver-patient relationship, and the patient's involvement in decision making. Support from caregivers during labor is correlated well with maternal satisfaction in other research studies 1,8,9. Another systematic review of prenatal and intrapartum interventions concluded that support for childbearing women, relaxation and pain relief during labor, minimizing obstetric interventions, and preparedness for birth were the most successful strategies for improving the childbirth experience 8.…”
mentioning
confidence: 77%
“…Support from caregivers during labor is correlated well with maternal satisfaction in other research studies. 1,8,9 Another systematic review of prenatal and intrapartum interventions concluded that support for childbearing women, relaxation and pain relief during labor, minimizing obstetric interventions, and preparedness for birth were the most successful strategies for improving the childbirth experience. 8 In a study of epidural decision-making, 3 themes were noted in interviews of study participants: concerns about personal safety for the mother-baby dyad; trust in health professionals; and previous experience with labor.…”
mentioning
confidence: 99%
“…Women’s dissatisfaction with maternity services during the pandemic was mostly associated with COVID-19 restrictions which resulted in prenatal health checks and birthing classes being cancelled, postponed, or performed through telemedicine clinics [ 23 ]. It has already been reported in the literature on childbirth satisfaction [ 24 , 25 ] and obstetric violence [ 26 , 27 ] before the COVID-19 pandemic that birth experience is influenced by factors such as lack of support from health professionals, perception of disrespect for expressed needs, and ineffective communication. Under ordinary conditions, these factors are known to be a disturbing interference which could impact the expected evolution of the physiological process of birth and the post-partum period, including lactation.…”
Section: Discussionmentioning
confidence: 99%
“…Quest'ultimo fenomeno è strettamente connesso alla modalità di alimentazione avviata nel punto nascita: il ricorso a sostituti del latte materno durante la degenza ospedaliera è un noto predittore di interruzione precoce dell'allattamento [28]. Inoltre è possibile ipotizzare che caratteristiche materne quali il grado di empowerment e self-efficacy incidano su entrambi i fenomeni [29][30][31][32]. Ciò fa sì che donne informate e consapevoli tendano più spesso ad avviare l'allattamento esclusivo e, di conseguenza, a ricevere meno frequentemente la prescrizione di formula artificiale alla dimissione.…”
Section: Discussioneunclassified